Study the Indicators of germination and growth of two varieties of papaya - Hussein Lafta Al-Seadi; Manal Zibari Sabti; Dhia Ahmad Taain (University of Thi-Qar Journal of agricultural research, 2023)
The study was conducted in the Seyhan Agricultural Reserve in the city of Siba in Basra Governorate during the period (2019-2021), for the purpose of knowing the extent of the success of the cultivation of Carica papaya L. and identifying the indicators of germination and growth of two varieties of local and Red lady papaya. Papaya seeds were grown under standard germination conditions.The results of the study showed the superiority of the Red Lady cultivar in the percentage of germination, seed germination speed and stem diameter, while the local cultivar was superior in seedling height.